2008
DOI: 10.1182/blood-2008-02-139824
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the TGF-β receptor I kinase promotes hematopoiesis in MDS

Abstract: MDS is characterized by ineffective hema- IntroductionThe myelodysplastic syndromes (MDSs) are clonal stem cell disorders characterized by cytologic dysplasia and ineffective hematopoiesis. [1][2][3] Although approximately one third of patients may progress to acute leukemia, refractory cytopenias are the principal cause of morbidity and mortality in patients with MDS. 4 In fact, approximately two-thirds of patients present with lower risk disease characterized by hypercellular marrows with increased rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 50 publications
6
121
4
1
Order By: Relevance
“…34 Moreover, it has been reported that hBMSC from patients with high-risk MDS show a significant increase of TGFB1. 35 However, Bhagat et al recently reported that increased activity of the TGFB pathway is common in MDS patients and that loss of inhibitory function of SMAD-7 is responsible for the dysplastic phenotype.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…34 Moreover, it has been reported that hBMSC from patients with high-risk MDS show a significant increase of TGFB1. 35 However, Bhagat et al recently reported that increased activity of the TGFB pathway is common in MDS patients and that loss of inhibitory function of SMAD-7 is responsible for the dysplastic phenotype.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…[56][57][58] Intriguingly, Zhou et al reported that SMAD2, a downstream mediator of TGF-β receptors, is constitutively activated and overexpressed in MDS BM precursors and that shRNA-mediated down-regulation or pharmacologic inhibition of TGF-β receptor 1 leads to enhanced hematopoiesis in a variety of MDS subtypes in vitro. 59 Thus, it is tempting to consider that the TGF-β signaling pathway inhibits leukemic transformation of MDS and that SETBP1 mutations contribute to the down-regulation of this important pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Individual datasets were obtained from seven independent studies (2, 26 -31) from NCBI Gene Expression Omnibus database, an on-line repository of all gene expression profiles reported in the literature (26). Methods to find and extract data have been described previously (32,33). The datasets were integrated based on UniGene identifications and were quantile-normalized to ensure cross-study comparability, based on our previous approach (32,33).…”
Section: Meta-analysis Of Mds and Normal Cd34 ϩ Gene Expression Studimentioning
confidence: 99%
“…Methods to find and extract data have been described previously (32,33). The datasets were integrated based on UniGene identifications and were quantile-normalized to ensure cross-study comparability, based on our previous approach (32,33). Analyses were performed using SAS (SAS Institute, Cary, NC) and the R language.…”
Section: Meta-analysis Of Mds and Normal Cd34 ϩ Gene Expression Studimentioning
confidence: 99%
See 1 more Smart Citation